Microcatheter Looping Technique Facilitates the Embolization of Complex Intracranial Aneurysms with an Acute Angle Branch Incorporated into the Sac - Xiaoxi, Zhang; Jing, Cai; Qinghai, Huang; Jianmin, Liu; Bo, Hong; Dongwei, Dai (World neurosurgery, 2017)
Intracranial aneurysms with an acutely angled parent vessel are difficult to enter using conventional techniques. This study examined efficacy, safety, and technical aspects of intraluminal, intra-aneurysmal, and in vitro microcatheter looping techniques (MLTs). MLTs were used to treat intracranial aneurysms with an incorporated acute angle branch in 29 consecutive patients after failed treatment with conventional techniques. The MLT was adopted based on specific morphologic traits of aneurysms and parent vessels. Narrow-necked aneurysms were generally treated with coiling alone, whereas wide-necked aneurysms and giant aneurysms were treated with stent-assisted coiling. Technical success was achieved in 28 of 29 cases (96.6%). In vitro MLT was used in 12 patients, intraluminal MLT was used in 14 patients, and intra-aneurysmal MLT was used in 3 patients. Immediate total occlusion was achieved in 8 patients, near-total occlusion was achieved in 8 patients, and subtotal occlusion was achieved in 13 patients. The MLT may provide access to an incorporated, acutely angled arterial branch that is difficult to enter using a conventional coiling technique. The in vitro MLT is potentially safer than intraluminal and intra-aneurysmal MLTs because the loop is very stable and requires less manipulation.